PELAKSANAAN DAN IMPLIKASI WIRID YASIN TERHADAP AKHLAK MASYARAKAT DI DUSUN ATU SEPIT KABUPATEN GAYO LUES - Kartini, Kartini; Riza, Syahrul (UIN Sumatera Utara Medan, 2025)
Wirid Yasin is a community gathering conducted based on mutual agreement without any compulsion. This activity serves not only as a form of worship but also as a medium for seeking knowledge, strengthening social ties, and fostering communal solidarity. This study aims to explore in depth the implementation of Wirid Yasin and its implications for the moral character of the community, as well as the supporting and inhibiting factors in shaping the morality of the people in Atu Sepit Hamlet, Ramung Musara Village, Gayo Lues Regency. The research employs a qualitative method with a descriptive approach. Data collection techniques include field observation, interviews, and documentation. The findings indicate that the regular and collective practice of Wirid Yasin has enhanced the spiritual awareness of the community, particularly among women. This activity has had a significant impact on moral development and the creation of social cohesion. Community members who participate sincerely and regularly demonstrate positive changes in attitudes and behavior. In contrast, those who are passive or attend without active participation show no significant behavioral change.